Political Communication Patterns of Young Adults in Germany - Datts, Mario; Wiederholz, Jan-Erik; Schultze, Martin; Vowe, Gerhard (Frontiers in Communication, 2021)
While the political communication and participation activities of young adults are changing, this is often not adequately captured by research due to a too narrow conceptualization of the phenomenon. Our approach conceptualizes political communication as activities comprising the reception of political content, interpersonal communication regarding political issues and political participation. On this basis, we investigated the patterns of political communication in the young generation and factors influencing the formation of different political communication patterns. Results of cluster analyses demonstrated that young adults in Germany should not be seen as a homogeneous group. Rather, we found six communication types. Interestingly, no online-only type of political communication was revealed. By applying multinomial logistic regression analysis, we were able to demonstrate that socio-demographic variables, individual resources and cognitive involvement in politics influence the likelihood of belonging to more active political communication types.